2023
DOI: 10.1001/jamapediatrics.2022.5848
|View full text |Cite
|
Sign up to set email alerts
|

Global Proportion of Disordered Eating in Children and Adolescents

Abstract: ImportanceThe 5-item Sick, Control, One, Fat, Food (SCOFF) questionnaire is the most widely used screening measure for eating disorders. However, no previous systematic review and meta-analysis determined the proportion of disordered eating among children and adolescents.ObjectiveTo establish the proportion among children and adolescents of disordered eating as assessed with the SCOFF tool.Data SourcesFour databases were systematically searched (PubMed, Scopus, Web of Science, and the Cochrane Library) with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 77 publications
(218 reference statements)
6
42
1
2
Order By: Relevance
“…Our findings indicated that female sex was linked with disordered eating. This result agrees with previous studies (2,21,22) but disagrees with others (23,47). Although sex differences in disordered eating are relatively minor in adolescence (50), these disorders are known to predominate among girls (2,51).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings indicated that female sex was linked with disordered eating. This result agrees with previous studies (2,21,22) but disagrees with others (23,47). Although sex differences in disordered eating are relatively minor in adolescence (50), these disorders are known to predominate among girls (2,51).…”
Section: Discussionsupporting
confidence: 83%
“…This result agrees with previous studies ( 2 , 21 , 22 ) but disagrees with others ( 23 , 47 ). Although sex differences in disordered eating are relatively minor in adolescence ( 50 ), these disorders are known to predominate among girls ( 2 , 51 ). Traditionally, studies have focused predominantly on the female sex, but currently, this has no longer been considered a girl-specific issue ( 51 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This relationship is significant for children rather than adolescents. Short sleep duration and sleep quality were significantly associated with overweight/obesity in girls, but not in boys in the same study [ 72 , 73 ]. Considering sleep quality, some studies have found that children and adolescents with poor sleep quality are more likely to gain weight [ 70 , 74 ], while other studies found no significant relationship between the two variables [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 94%